Particle tracking using micro bubbles in bubbly flows. (22nd October 2016) - Ziegenhein, T.; Garcon, M.; Lucas, D.
Abstract: Micro bubbles do not contaminate multiphase flows like additional tracer particles so that the velocity in such can be determined completely non-intrusive by tracking them. They are, however, often larger as conventional tracer particles and have a significantly different density than the surrounding fluid. The usability of micro bubbles as tracers in bubbly flows, particularly in buoyancy driven flows, is investigated in this work. The results are compared to particle image velocimetry measurements using PMMA tracer particles. In combination with the used volume illumination, a simple, robust and reliable measuring technique is discussed, which is deployable for complex problems like photo bioreactors or submerged oceanic multiphase flows. Averaged liquid velocities as well as basic turbulence parameters are determined in a rectangular bubble column for different gas volume flow rates. High flow rates are good manageable due to the volume illumination whereas the PIV measurements using a light sheet are approaching to their limits. The general sampling bias in multiphase flows found recently for PIV measurements is also present for particle tracking methods; a hold processor that waits a time depending on the distribution of the particle information over the measuring area gives reasonable results. Highlights: Non-intrusive liquid velocity measurements in bubbly flows. Particle tracking velocimetry (PTV) for high void fractions. Sampling bias in bubbly flows for PTV is described. Very simple, cheap and robust measuring method. Particle tracking velocimetry is compared to particle image velocimetry.